A metabolomic study on the anti-depressive effects of two active components from Chrysanthemum morifolium - Tong Liu; Ning Zhou; Ruihao Xu; Yangang Cao; Yanli Zhang; Zhen Liu; Xiaoke Zheng; Weisheng Feng (Artificial Cells, Nanomedicine, and Biotechnology)
Chrysanthemum morifolium (Chr) is a traditional Chinese medicine (TCM) that has been used in the treatment of inflammation-linked diseases for hundreds of years. Naringenin (Nar) and apigenin (Api) are the major active components in aqueous extracts of C. morifolium. The aim of our study was to clarify the roles of Chr, Nar and Api in ameliorating depression-like behaviour induced by corticosterone. First, the behavioural and biochemical indicators closely related to depression were examined to evaluate the therapeutic effects of Chr/Nar/Api on a depression model. Then, a metabolomics approach was utilized to screen for biomarkers and related pathways between a control group and Chr/Nar/Api groups. The comprehensive results revealed that Chr/Nar/Api exerted anti-depressant effects through interfering with tryptophan metabolism, arginine and prolinemetabolism, citrate cycle, niacin and niacinamide metabolism, phenylalanine metabolism, and alanine, aspartate and glutamate metabolism. The mechanism of Chr/Api/Nar in the treatment of depression was elucidated based on material and energy metabolism. Moreover, Nar could be used as a substitute for Chr for reversing depression-like behaviour, and Api was similar to a positive drug in terms of function on depression. The integrated metabolomics approach demonstrated here should be an effective method for interpreting the function of herbs from TCM and clarifying the mechanism of their components in future studies.